Seeing empowerment as relational: lessons from women participating in development projects in Cambodia. Issue 2 (17th February 2020) - Doneys, Philippe; Doane, Donna L.; Norm, Sina
ABSTRACT: This article explores how empowerment is understood locally, and whether low-income Cambodian women perceive they are empowered in that sense. Interview data from 120 participants in empowerment projects show that although some forms of empowerment as defined by donor agencies occur, such as through increases in knowledge, self-confidence, and decision-making ability, empowerment is rarely understood by the women themselves in individual terms. Instead, empowerment is seen as contributing to and gaining respect from others, including partners, family and community members, yet not always in line with traditional gender roles. Recommendations are provided to acknowledge these findings.